PENGEMBANGAN SISTEM INFORMASI SISWA BERBASIS WEB DENGAN DASHBOARD INTERAKTIF UNTUK MONITORING DATA AKADEMIK DI SDK WEELONDA - Oktavianus Bili,; Trisno,; Lidia Lali Momo, (Indonesian Journal of Engineering and Computer Science (IJEC), 2025)
Advances in information technology have recently been growing rapidly, especially with the increasing prevalence of the internet among an increasingly global society. In Southwest Sumba Regency, several educational institutions, both public and private, have yet to utilize existing technology due to limited facilities and human resources. One such institution is SDK Weelonda. SDK Weelonda is an educational institution tasked with handling activities related to education, with the main goal, as is known, to educate the nation. To address the aforementioned obstacles or problems, researchers propose a web-based information system using an interactive dashboard. An interactive dashboard is a visual display that presents data and information concisely, dynamically, and easily understood. Based on these problems, the researchers are interested in providing a solution through writing a proposal entitled: Development of a Web-Based Student Information System with an Interactive Dashboard for Monitoring Academic Data at SDK Weelonda. The web-based student data information system at SDK Weelonda makes it easier for the school to manage all student and teacher data.